A Phase III trial to investigate the timing of radiotherapy for prostate cancer with high‐risk features: background and rationale of the Radiotherapy – Adjuvant Versus Early Salvage (RAVES) trial. (March 2014) - Pearse, Maria; Fraser‐Browne, Carol; Davis, Ian D.; Duchesne, Gillian M.; Fisher, Richard; Frydenberg, Mark; Haworth, Annette; Jose, Chakiath; Joseph, David J.; Lim, Tee S.; Matthews, John; Millar, Jeremy; et al.
Abstract : Objectives: To test the hypothesis that observation with early salvage radiotherapy (SRT) is not inferior to 'standard' treatment with adjuvant RT (ART) with respect to biochemical failure in patients with pT3 disease and/or positive surgical margins (SMs) after radical prostatectomy (RP). To compare the following secondary endpoints between the two arms: patient‐reported outcomes, adverse events, biochemical failure‐free survival, overall survival, disease‐specific survival, time to distant failure, time to local failure, cost utility analysis, quality adjusted life years and time to androgen deprivation. Patients and Methods: The Radiotherapy – Adjuvant Versus Early Salvage (RAVES) trial is a phase III multicentre randomised controlled trial led by the Trans Tasman Radiation Oncology Group (TROG), in collaboration with the Urological Society of Australia and New Zealand (USANZ), and the Australian and New Zealand Urogenital and Prostate Cancer Trials Group (ANZUP). In all, 470 patients are planned to be randomised 1:1 to either ART commenced at ≤4 months of RP (standard of care) or close observation with early SRT triggered by a PSA level of >0.20 ng/mL (experimental arm). Eligible patients have had a RP for adenocarcinoma of the prostate with at least one of the following risk factors: positive SMs ± extraprostatic extension ± seminal vesicle involvement. The postoperative PSA level must be ≤0.10 ng/mL. Rigorous investigator credentialing and a quality assurance programme are designed to promote consistent RT delivery among patients. Results: Trial is currently underway, with 258 patients randomised as of 31 October 2013. International collaborations have developed, including a planned meta‐analysis to be undertaken with the UK Medical Research Council/National Cancer Institute of Canada Clinical Trials Group RADICALS (Radiotherapy and Androgen Deprivation In Combination with Local Surgery) trial and an innovative psycho‐oncology sub‐study to investigate a patient decision aid resource. Conclusion: On the current evidence available, it remains unclear if ART is equivalent or superior to observation with early SRT.